2011
DOI: 10.12659/msm.881834
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, treatment and outcome of glutaric aciduria type I in Zhejiang Province, China

Abstract: SummaryBackgroundGlutaric aciduria type I (GA I; MIM 231670) is a rare autosomal recessive disorder resulting from glutaryl-CoA dehydrogenase deficiency. This article reports our experience in the diagnosis, treatment and outcome of GA I patients in Zhejiang Province, China.Material/MethodsA total of 129,415 newborns (accounting for approximately one-tenth of the annual births in Zhejiang Province) and 9640 high-risk infants were screened for inborn errors of metabolism in the Neonatal Screening Center of Zhej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…More than 20 years later evidence has increased that early diagnosis and treatment is beneficial. 1,6,15,16,[18][19][20]27,28,[30][31][32][33] This meta-analysis unequivocally confirms that patients identified by NBS show a superior neurologic outcome with a higher rate of normal motor development and a lower rate of acute or insidious onset of MD compared with patients identified by TMS. Accordingly, it is a significant progress that a growing number of countries worldwide (e.g., 17 have meanwhile included GA1 in their national NBS programs or NBS pilot studies 23 and this study will hopefully guide the decision of governments of those countries who have not so far.…”
Section: Nbs Improves the Neurological Outcome Of Individuals With Ga1supporting
confidence: 64%
See 3 more Smart Citations
“…More than 20 years later evidence has increased that early diagnosis and treatment is beneficial. 1,6,15,16,[18][19][20]27,28,[30][31][32][33] This meta-analysis unequivocally confirms that patients identified by NBS show a superior neurologic outcome with a higher rate of normal motor development and a lower rate of acute or insidious onset of MD compared with patients identified by TMS. Accordingly, it is a significant progress that a growing number of countries worldwide (e.g., 17 have meanwhile included GA1 in their national NBS programs or NBS pilot studies 23 and this study will hopefully guide the decision of governments of those countries who have not so far.…”
Section: Nbs Improves the Neurological Outcome Of Individuals With Ga1supporting
confidence: 64%
“…Finally, a total of 15 publications 1,6,15,16,[18][19][20][21][27][28][29][30][31][32][33] reporting on more than one NBS patient were included into quantitative synthesis ( Fig. 1, Table S2) covering 11 populations in nine countries and two multinational publications (with patients from 37 6 and 16 countries, 29 respectively), of which 11 studies 1,6,15,18,20,[27][28][29][31][32][33] also reported on patients identified by TMS (Table S3). Overall, reports on 647 GA1 patients were included in the analysis.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…The Newborn Screening Center of Zhejiang Province is the largest screening center in China, and initially implemented MS/MS for screening 26 treatable metabolic disorders in symptomatic infants in 2008, and expanded this to newborn screening in 2009. However, MS/MS newborn screening is not currently mandatory, and only 10% of annual births in Zhejiang Province are screened [ 2 ] Samples from symptomatic patients with suspected IEM from throughout the province and neighboring provinces are sent to the Newborn Screening Center of Zhejiang Province. The cost of MS/MS screening in symptomatic infants is 390 RMB (around $59.72).…”
Section: Introductionmentioning
confidence: 99%